Does Late Childbearing Increase the Risk for Behavioural Problems in Children? A Longitudinal Cohort Study. Issue 1 (9th December 2014) - Tearne, Jessica E.; Robinson, Monique; Jacoby, Peter; Li, Jianghong; Newnham, John; McLean, Neil
Abstract Background This study aimed to examine the relationship between advanced parental age and behavioural outcomes in offspring in a longitudinal cohort of children in Western Australia. Methods The Western Australian Pregnancy Cohort (Raine) is a prospective study of 2900 pregnancies. Offspring were followed up at ages 2, 5, 8, 10, 14, and 17 years, and 1754 adolescents were available for follow‐up at 17 years. The Child Behaviour Checklist was used to measure child behaviour, including internalising (e.g. anxious/withdrawn) and externalising (e.g. aggressive/destructive) behaviours. Results There was a significant linear relationship between maternal age and total internalising and externalising behaviour outcomes, but not paternal age. Increasing maternal age was associated with decreasing risk for problem behaviours in offspring. In the categorical models, young maternal age (20–24 years) was associated with significantly increased risk for problem behaviours in offspring relative to offspring of parents in the reference group (25–29 years), and a paternal age of 35–39 years was associated with decreased risk for total behaviour morbidity in offspring. Conclusions This study showed no evidence that late fatherhood is associated with adverse behavioural outcomes in offspring. Increasing maternal age was found to be a protective factor for child behaviour morbidity.